Comparison of familial clustering of anogenital and skin cancers between in situ and invasive types - Zhang, Luyao; Hemminki, Otto; Zheng, Guoqiao; Försti, Asta; Sundquist, Kristina; Sundquist, Jan; Hemminki, Kari (Scientific reports, 2019)
Literature on familial risk of carcinomas in situ (CISs) is limited because many cancer registries do not collect information on CIS. In Sweden CISs are collected, and we used these data to analyze familial relative risks (RRs) for concordant (CIS-CIS) types of anogenital (cervical, other female and male genital and anal) and skin squamous cell CIS; additionally RRs were assessed between CIS types and between CIS and invasive forms. RRs were calculated for the offspring generations when family members were diagnosed CIS. Case numbers for CIS ranged from 330 in anal to 177,285 in cervical CIS. Significant concordant CIS-CIS RRs were 2.74 for female genital, 1.77 for cervical and 2.29 for SCC skin CISs. The CIS forms associated also with each other, except for cervical and skin CIS types. RRs for concordant CIS-invasive cancer associations were lower than CIS-CIS associations. Cervical CIS associated with non-Hodgkin CIS which may suggest immune dysfunction as a contributing factors. The results for anogenital CIS types suggest that life style related human papilloma virus infections contributed to the observed familial associations. Lower risks for CIS-invasive cancer than CIS-CIS suggest that CIS and invasive cancers share only partially risk factors that underlie familial clustering.
Gesehen am 05.12.2019